Photonic antenna for long range wireless communication - Ngah, Razali (Penerbit UTM, 2008)
Wireless access network is a very popular and famous technology in today’s communication world. Wireless access, either fixed or mobile is regarded as an excellent way to achieve good broadband services. The future generation of cellular networks will need much smaller cells than present generation networks and Radio over Fiber (RoF) technology and photonic antenna are introduced for this application. However, photonic antennas proposed in some publications generally are intended for short range communication. This chapter presents design and simulation of photonic antenna for longer range application. The antenna is designed for 5.8 GHz, as the operating frequency is commonly used for long range, WLAN backhaul network. Overview on RoF technology and photonic antenna are also presented in this chapter.